Using an Expectancy-Value Model to Understand Teaching Motivation among Nontraditional Preservice Teachers: A Phenomenological Study Approach. (3rd April 2018) - Thomson, Margareta Maria; Palermo, Corey J.
ABSTRACT: This qualitative study used a phenomenological methodology and an expectancy-value framework to understand nontraditional preservice teachers' motivations for choosing a teaching career. Nontraditional preservice teachers in the current study are described as teacher candidates for whom teaching was not their first career choice. Ten students enrolled in a Master of Arts in Teaching (MAT) program in the United States participated in in-depth, semistructured interviews about their decisions to become teachers. Analyses revealed five thematic concepts that illustrated how participants described their entry to the teacher education program. These themes related to participants' ability beliefs and expectancies, personal utility values, intrinsic values, social utility values, and the costs associated with choosing a teaching career. Implications for teacher education and mentoring programs are discussed.